Aneurysm of Right Sinus of Valsalva: A Particular Case Report and Brief Review of Literature - NUNZIATA, LUIGI; Ambrosino, Saverio; Volpicelli, Mario; Capasso, Michele; Caliendo, Luigi (International Journal of Innovative Research in Medical Science, 2023)
The aneurysms of sinus of Valsalva are rare cardiac anomalies, which may be either acquired or congenital. A congenital lack of continuity between the aortic media and annulus fibrosus may initiate aneurysm formation. Acquired aneurysms may result from trauma, endocarditis, syphilis, Behcet, atherosclerosis and senile-type dilatation. We report a case of a 38-year-old man who presented with aneurysm of the right sinus of Valsalva with fistula between it and the right ventricular outflow and pulmonary trunk dilatation diagnosed by transthoracic echocardiography (TTE), chest computed tomography (CT) scan and transesophageal ecocardiography (TEE). We describe this case which has been successfully-treated because the concomitant presence of an aneurysm of the right Valsalva sinus, a fistula between it and the right ventricular outflow and pulmonary trunk dilatation represents an extremely rare and poorly described event in the literature.